Headphone use and hearing in medical students at a public university in Lima, Peru: Uso de auriculares y la audición en estudiantes de medicina de una universidad pública de Lima, Perú - Cordero-Pinedo, Félix (2024)
Introduction: Hearing loss affects millions globally, especially young people who frequently use headphones. Objective: To establish the relationship between headphone use and hearing among medical students in Lima, Peru. Methods: An observational, analytical, and cross-sectional study was conducted at the Universidad Nacional Federico Villarreal. Participants included 98 medical students (18-32 years) who regularly used headphones. Those with previous hearing pathologies were excluded. Data collection included surveys on headphone use and audiometries performed in a silent booth. Results were analyzed using descriptive and inferential statistics, employing the Spearman's Rho correlation coefficient to assess the relationship between variables. Results: 59.2% of the students were women. 39.2% had mild hearing loss at high tones, while 36.2% had normal hearing. 71.4% reported decreased hearing capacity, and 56.1% experienced ear pain. Headphone use showed a positive and significant correlation with hearing (Rho = 0.298, p = 0.003). Exposure time was also significant (Rho = 0.260, p = 0.010), but sound intensity was not (Rho = 0.193, p = 0.057). Conclusion: There is a positive relationship between headphone use and hearing loss in medical students. It is recommended to implement awareness programs on safe headphone use and conduct regular hearing evaluations to prevent auditory deterioration.